Factors Associated with Chronic Noncancer Pain in the Canadian Population - Saifudin Rashiq; Bruce D Dick (Pain Research and Management)
Chronic noncancer pain (CNCP) is a prevalent health problem with pervasive negative effects on the individual’s quality of life. Previous epidemiological studies of CNCP have suggested a number of individual biological, psychological and societal correlates of CNCP, but it has rarely been possible to simultaneously compare the relative strengths of many such correlates in a Canadian population sample. With data provided by the 1996/1997 Canadian National Population Health Survey, ordinal logistic regression was used to examine the extent to which a number of population variables are associated with CNCP in a large (n=69,365) dataset. The analysis revealed cross-sectional correlations of varying strengths between CNCP and 27 factors. Increasing age, low income, low educational achievement, daily cigarette smoking, physical inactivity and abstention from alcohol were among the factors found to increase CNCP risk. The considerable impact of distress and depression on CNCP are also highlighted. A number of comorbid medical illnesses increased CNCP risk, including some (such as chronic obstructive pulmonary disease, epilepsy and thyroid disease) that have not hitherto been associated with pain. White race and the affirmation of an important role for spirituality or faith reduced CNCP risk. In contrast to some previous studies, female sex did not emerge as an independent CNCP risk. The present exploratory analysis describes associations between CNCP and a number of characteristics from several domains, thus suggesting many areas for further research.